OPTIMIZATION OF ELECTROCOAGULATION PROCESS FOR LEAD REMOVAL FROM MINING LAKE WATER AND ITS ADSORPTION STUDIES - ORJI,, KALU UKA (2015)
Exposure of tin ore and the associated minerals such as galena (PbS), arsenopyrite (FeAsS). chalcopyrite (CuFeS2), stannite (Cu2FeSnS4), teal!ite (PbSnS2), pyrite (FeS), etc to air during mining might cause the oxidation and dissolution of the minerals which lead to the release of heavy metals to the mining lake. One of such heavy metals is lead. Mining lake water was reported to contain lead as high as 69.46 mgL·1 • Consumption of water containing Pb can cause toxic effects to humans. including brain damage. This is the reason mining lake water is not recommended as drinking water source. The conventional treatment of water does not easily remove Pb from water. A promising and emerging treatment technology for Pb removal is by the application of electrocoagulation.